UJI AKTIVITAS EKSTRAK ETANOL DAUN KETAPANG (Terminaliacatappa) SEBAGAI ANTIBAKTERI TERHADAP PERTUMBUHAN Escherichia coli DAN Staphylococcus aureus SECARA IN VITRO - Leonardo A. Seme; Elisabet Tangkonda; Nemay A Ndaong (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
Collibacilocis is a disease which is caused by Escherichia coli. Staphylococcus aureus is one of bacterial species which is cause mastitis. Antibiotic can be use to treat a disease which is caused by Escherichia coli dan Staphylococcus aureus infection. Antibiotic can cause a side effect such as bacteria resistance and reside to from animal. Cattapa leaves contain flavonoid, alkaloid, tannin, triterpenoid, resin, and saponin compound which is have function as antibacterial. The aim of this study is to know the effects of cattapa leaves ethanol extract for growth of Escherichia coli and Staphylococcus aureus. This study use bacterial from envirionment that isolated from pig with diarrhea sample and Staphylococcus aureus from cow that show mastitis symptoms. This study consist two group are treatment group and comparator group. Treatment group are cattapa leaves ethanol extract that given of 20%, 40%, 60%,80%, and 100%. The comparator group are antibiotic group that consist of ciprofloksasin, tetracycline, cefoxitin, amoxicilin, and ampicilin. The study result show cattapa leaves ethanol extract do not have effect to inhibite growth of Escherichia coli and Staphylococcus aureus. The conclusion is cattapa leaves do not have effect to inhibits the growth of Escherichia coli dan Staphylococcus aureus.